Unmanned Aerial Vehicle (UAV) Photogrammetry Technology for Dynamic Mining Subsidence Monitoring and Parameter Inversion: A Case Study in China - Dawei, Zhou; Lizhuang, Qi; Demin, Zhang; Baohui, Zhou; Lianglin, Guo (IEEE access, 2020)
This study mainly presents the method for monitoring the surface dynamic subsidence basin (SDSB) caused by underground coal mining and obtaining parameters of mining subsidence (PMS) in the short term by using an unmanned aerial vehicle (UAV) Photogrammetry Technology. The basic ideas and methods are proposed; that is, the two-stage surface digital elevation model (DEM) is obtained in the short term by UAV; The SDSB is obtained through two phases of DEM subtraction; Based on the dynamic inversion method established in this study, the PMS was obtained. The UAV method was used to monitor the Wangjiata coal mine in Inner Mongolia of China three times in three months to obtain the three phases of DEM; we obtained the two phases SDSB by the three phases of DEM subtraction. The accuracy of DEM and SDSB were 118 mm and 121 mm respectively, Although the accuracy cannot fulfill the requirements of mining subsidence, the PMS was obtained by dynamic inversion method of full subsidence basin fitting, which has better resistance to errors; hence, the obtained PMS are reliable. Based on the engineering application, this study concludes that as a new technology, UAV photogrammetry technology can obtain the SDSB of coal mining areas in a short period with reliable PMS. Meanwhile, it has the advantages of low cost, flexible maneuverability, and so on, and overcomes the shortages of traditional observation stations, which has long observation time and high labor intensity, needs to bury fixed measuring points and easily lose them, and just has a small amount of "spot-like" observation data that cannot reflect the deformation characteristics of the whole subsidence basin. Furthermore, it is feasible to apply this method to mining subsidence monitoring and parameter inversion, and it has a great application prospect for the mining area purposes.